Pro iOS design and development HTML5, CSS3, and JavaScript with Safari - Picchi, Andrea (Apress, 2011)
With Pro iOS Web Design and Development, you'll design websites and develop web applications for iPhone and iPad using web standards deployed with Apple's Safari browser. Utilizing the very latest web and mobile technologies and releases, this book shows every web professional how to use HTML5 to do the heavy lifting, CSS3 to create the look and feel, and JavaScript to add program logic to their mobile sites and Web applications. In addition, you'll learn how to address the specific features made available through Apple's iOS, especially with regard to designing Web-based touch-screen interfaces. Pro iOS Web Design and Development will help you deliver rich mobile user experiences without compromise by optimizing your sites for WebKit and Safari, the de facto standard for the iPhone, iPad, and iPod touch